Compact and unified elasto-plastic formulation to study isotropic plates - Mantari J.L. (2020)
We introduce a compact and unified shear deformation theory for plates with elasto-plastic behavior. We formulate the kinematics of the two-dimensional structure in a compact and unified manner using the Carrera Unified Formulation. This formulation allows for generalized expansions of the primary variables and through-the-thickness functions. We obtain the governing equations using the principle of virtual work and a finite element discretization. We solve the nonlinear equations using a Newton–Raphson linearization scheme, and linearize the constitutive equations using the algorithmic tangent moduli. We consider the J2 flow theory of plasticity, and use a backwards Euler scheme to update the stresses. We analyze the convergence, and compare the effectiveness of the Mixed Interpolation of Tensorial Components technique in contrasting the shear locking phenomenon in the nonlinear regime to the use of full and uniform reduced integration. We also conduct numerical assessments for plates under uniform and line loads. We compare the present results to those obtained by finite element commercial software, and demonstrate the computational efficiency of the present method. © 2019